2013
DOI: 10.1155/2013/259454
|View full text |Cite
|
Sign up to set email alerts
|

Serum Circulating microRNA Profiling for Identification of Potential Breast Cancer Biomarkers

Abstract: MicroRNAs (miRNAs) are a class of small, non-coding RNA molecules that can regulate gene expression, thereby affecting crucial processes in cancer development. miRNAs offer great potential as biomarkers for cancer detection because of their remarkable stability in blood and their characteristic expression in different diseases. We investigated whether quantitative RT-PCR miRNA profiling on serum could discriminate between breast cancer patients and healthy controls. We performed miRNA profiling on serum from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
171
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 38 publications
(41 reference statements)
14
171
5
1
Order By: Relevance
“…Therefore, we hypothesized that these miRNAs might be candidates for noninvasive breast cancer detection. Overexpression of circulating miR-21-5p has been described in breast cancer patients (27)(28)(29)(30) but also in other cancers such as esophageal, gastric, colorectal, and lung (31 ). This result shows the potential utility of circulating miR-21-5p as a broadspectrum biomarker for the detection of various cancers and not specifically for breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, we hypothesized that these miRNAs might be candidates for noninvasive breast cancer detection. Overexpression of circulating miR-21-5p has been described in breast cancer patients (27)(28)(29)(30) but also in other cancers such as esophageal, gastric, colorectal, and lung (31 ). This result shows the potential utility of circulating miR-21-5p as a broadspectrum biomarker for the detection of various cancers and not specifically for breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 83%
“…This result shows the potential utility of circulating miR-21-5p as a broadspectrum biomarker for the detection of various cancers and not specifically for breast cancer diagnosis. MiR125b-5p has also been reported to be upregulated in the serum of breast cancer patients (28,32 ) and has been associated with chemotherapeutic resistance, nonresponsive patients having higher expression levels. Finally, upregulation of miR-96-5p and downregulation of miR-505-5p have been reported in breast tumors and related to increased cell proliferation (33,34 ), but this is the first time that their circulating levels are associated with breast cancer, both being overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…miR-184 was observed to be highly expressed in prostate cancer, while it was significantly downregulated in renal cell carcinoma patients, and was not correlated with patient age and gender or clinical stage of renal cell carcinoma (23). The study by Mar-Aguilar et al confirmed the upregulation of miR-382 in the serum of patients with breast cancer; a sensitivity of 94.40% and a specificity of 90.00% was found for the diagnosis of breast cancer (24). A study by Li et al showed that miR-382-5p expression was significantly downregulated in patients with ductal carcinoma in situ (25), while miR-1246 was demonstrated to exhibit high expression in colorectal cancer (26), esophageal squamous cell carcinoma (27), cervical carcinoma (28), hepatocellular carcinoma (29) and other cancers.…”
Section: A B C Dmentioning
confidence: 95%
“…Multiple studies (Table 3) have demonstrated that miRNA biomarkers provide excellent sensitivity and specificity for detecting early-and even advancedstage breast cancer, strongly suggesting that they are potential diagnostic tools for identifying early and advanced breast cancers [206][207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224]. The most commonly reported miRNAs in body fluids and best candidates for biomarkers are miR-21, miR-155, miR-10 b, miR-92 a, miR-133 a, miR-145, miR-148 b and miR-451 [207,[211][212][213][214][215][216][217][219][220][221][222][223]. It is worthy to note that among these identified diagnostic miRNA biomarkers, three miRNAs, including miR-195, miR-145 and miR-451, were reported to be breast cancer specific and can be potentially exploited to distinguish breast cancer from other types of cancer [206,219].…”
Section: Translational Implications Of Ncrnas In Breast Cancermentioning
confidence: 99%